Malaria and Dengue: Understanding two infectious diseases affecting developing countries and their link to climate change - Mirza Alas (South Centre, 2021)
Developing countries will face more complex challenges as infectious disease patterns transform due to climate change and climate variability. These challenges include how to reduce the incidence of malaria (including the significant challenge of resistant malaria), dengue, and other vector-borne and water-borne diseases that are likely to experience alterations in geographical range and lengthening of the transmission seasons due to changing temperatures and rain patterns. Climate extremes, e.g., heat and floods, are implicating the spread of climate-sensitive infectious diseases such as dengue and malaria transmitted by vectors like mosquitoes. In the context of growing financial pressure on governments due to COVID-19, the ensuing fiscal challenges may severely limit the capacity to effectively respond to health challenges in countries already affected by malaria and dengue. Other countries that have made gains in controlling vector-borne infections could also be vulnerable to rising disease burden. This research paper aims to analyze how changes in malaria and dengue pose a challenge for developing countries as they prepare mitigation and adaptation strategies for climate health. The paper will also provide some general recommendations on the importance of integration of health in national climate change strategies.
Keywords: 300; Adaptation; Brazil; Climate Change; COVID-19; Dengue; Health; Kenya; Malaria; Mitigation; National Adaptation Plans (NAPs); Pandemic; Vector-Borne Diseases